Ultra-Wideband Trident Inset-Fed Monopole Antenna With a 3-D Conical Ground - Philip Ayiku Dzagbletey (IEEE Access, 2021)
An ultra-wideband antenna with a conical ground and trident inset feeding structure is presented. The antenna consists of a U-shaped monopole designed on a printed circuit board and a three-dimensional conical aluminium mold, serving as the ground. Low frequency (<; 1 GHz) matching is achieved with the trident feed branches by inserting them into the monopole. Simulation studies show that the proposed 3-D conical ground outperforms horizontal or flat-lying ground models in terms of impedance matching bandwidth and radiation pattern omni-directivity. The 3-D ground also helps to stably mount the antenna in a measurement facility. Simulation and measured results presented in this paper demonstrate that the proposed antenna is suitable as a testing antenna with omnidirectional radiation patterns over a broad bandwidth. A 14.6:1 bandwidth ratio (0.56 - 8.2 GHz) has been realized at a voltage standing wave ratio below 2:1 with antenna gain above 2 dBi.